Christian Pelras And His Work: 17 August 1934–19 July 2014 - Macknight, Campbell (Penerbit Universiti Sains Malaysia (USM Press), 2016)
Those of us who work in the human sciences are, of necessity, involved with the task of interpretation: interpreting the past to the present, interpreting the ways of "others" to our own society, or even interpreting our own society to itself. Bugis society in the second half of the 20th century was fortunate indeed to have had Christian Pelras as its interpreter. He himself describes the work of ethnology as "a dialogue between our culture and the culture of others" (Pelras 2010: 7). For the most part, he wrote for a scholarly Francophone audience but, as time went on, more of his writing appeared in English and some in Indonesian. A strength of Pelras' work in Indonesia was his thorough education in western European culture, including its languages and literature. He had a firm foundation from which to conduct his "dialogue," and the dialogue went both ways. His research career in Indonesia was inter-twined with a parallel interest in Brittany. In December 1961, he returned from almost a year in Indonesia, his first visit, and was soon engaged in an interdisciplinary project at home. Much of the next few years were spent in Goulien, a tiny village in the extreme northwest corner of France, and his doctoral thesis, completed in 1966, deals with this research. A revised version, incorporating new fieldwork, was published in 2001. His memory is much cherished in Goulien and in November 2014 the new local library was named in his honour.